Umngqokolo: Xhosa overtone singing and the song nondel'ekhaya - Dargie, David (International Library of African Music, 2017)
This type of gruff singing 'vocal percussion' is also used by young men in the Lumko district, but there is another kind of umngqokolo - that used by women and girls - which is a form of overtone singing. At the time of writing (1985), Lumko Missiological Institute was situated at Lumko Mission, 12 kilometres south of Lady Frere, which is a small town some 48 kilometres east of the Cape Province town of Queensland. The name "Lumko”, which means 'wisdom', is in fact the name of the family which once owned Lumko as part of their farm.
Keywords: African Music